Implementation of the POE2WE Model in Classroom Action Research Training to Enhance Teacher Competence at a Quranic Science Boarding School - Nana, Nana; Susanti, Ernita; Makiyah, Yanti Sofi; Sulistyaningsih, Dwi; Sumantri, Agus; Suniah, Cici Nabila; Filiyani, Rosa; Isani, Julia; Komarudin, Nanang (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Classroom Action Research (CAR) enables teachers to enhance teaching quality and student achievement. In Tasikmalaya Regency, however, many teachers need help to develop CAR effectively, impacting learning outcomes. To address this, a CAR training program utilizing the POE2WE (Predict, Observe, Explain, Elaborate, Write, Evaluate) model was implemented through the Participatory Action Research (PAR) approach, fostering active teacher engagement. The training, targeting high school teachers in Tasikmalaya, focused on equipping participants to develop high-quality CAR. Results indicated significant improvements in teacher competence, with participants achieving high ratings in critical skills: discussion activity (3.8), prediction formulation (3.7), and self-evaluation (3.9). Over 90% of participants expressed satisfaction with training materials, instructor competency, and the applicability of theory to practice. These findings underscore the value of structured CAR skills enhancement for educational development in Tasikmalaya and beyond, recommending that future programs adopt adaptable models to meet evolving teacher needs in classroom outcomes.Top of Form